The modelling and design optimisation of sawdust, garnet waste, and palm oil fuel ash-based hybrid asphalt binders using response surface methodology - Wan Noor Hin, Mior Sani; Putra Jaya, Ramadhansyah; Mawardi, Indra; Zaid Hazim, Al-Saffar; Haryati, Yaacob (Elsevier B.V., 2026)
This study evaluated the rheological characteristics of a hybrid asphalt binder integrating sawdust, garnet waste, and palm oil fuel ash (POFA). Approximately 0 %, 3 %, 6 %, and 9 % of hybrid materials were incorporated into the unaged and rolling thin film oven (RTFO) hybrid asphalt binders were assessed. Furthermore, the central composite design (CCD) in the response surface methodology (RSM) were utilised to evaluate the effects of hybrid asphalt binder content and temperature on the rheological behaviour of the hybrid asphalt binders. Consequently, the hybrid asphalt binders showed dosage-dependent rheological behaviour, with the 6 % formulation exhibiting notably lower phase angle (δ) and complex shear modulus (G∗) than the control binder, particularly in the unaged state, while other dosages displayed more variable responses across the tested temperatures. The RTFO hybrid asphalt binders also revealed reduced stiffness across all temperatures compared to the control asphalt. Given that high correlation coefficients (R2) were demonstrated by the G∗ (<0.97) and δ (<0.93), a substantial relationship between the model values and the experimental data was identified. The optimal parameters (temperature and percentage) for the hybrid materials were also discovered to be 62.9 °C and 5.78 % using the numerical optimisation and the quadratic model. Considering that each response possessed a percentage error below 5 %, the effectiveness and the validation of the model were successfully verified in this study.